X-linked hypophosphatemic rickets and nephrocalcinosis: clinical characteristics of a single-center pediatric cohort in North America before and after burosumab - Paloian, Neil J.; Boyke-Lohmann, Lindsey R.; Steiner, Robert D. (Frontiers in Pediatrics, 2024)
Background X-linked hypophosphatemic rickets (XLH) is a rare genetic disease characterized by inappropriately elevated circulating fibroblast growth factor 23 (FGF-23) and subsequent urinary phosphate wasting. The primary clinical manifestations of XLH include short stature, lower extremity bowing, dental abscesses, and rickets. Historical treatment includes phosphate and vitamin D supplementation, but recently, targeted therapy with burosumab has gained widespread acceptance. Burosumab is an FGF-23 blocking antibody. Conventional therapy options have been associated with the development of nephrocalcinosis (NC), with reported rates varying between 33% and 80% in XLH patients. Previous studies have noted that the phosphate supplementation dose correlates with the presence of NC, although this finding is not consistent across studies. It remains unclear whether nephrocalcinosis occurs in patients now treated with burosumab. Our aim was to identify XLH-associated nephrocalcinosis risk factors in our cohort of children with XLH and provide an updated analysis in the era of burosumab. Methods We identified 13 children with XLH who received routine medical care for XLH at our institution between 2015 and 2023. All were initially treated with conventional therapy and were transitioned to burosumab either upon its US Food and Drug Administration (FDA) approval in 2018 or at 6 months of age if this occurred after 2018. All patients were routinely monitored and this included laboratory tests and renal ultrasonography. Phosphate and calcitriol dosages were regularly adjusted to minimize serum and urinary laboratory abnormalities. Burosumab was administered according to its FDA package insert directions. Medication doses and laboratory values were analyzed between the group with NC and the group without NC. Results Three patients were noted to have evidence of NC within the study timeline. Two children developed NC while receiving conventional therapy and one while prescribed burosumab. None of the variables, including a positive family history of XLH, average age at diagnosis of XLH, duration or dosage of treatment with conventional therapy, average age at the initiation of burosumab, and all measured laboratory values, were significantly different between the groups with and without NC. Female sex was the only identified significant risk factor for a diagnosis of XLH-associated NC. Conclusion XLH-associated NC remains a clinical concern even with modern treatment, although the traditional risk factors (dose of phosphate supplements and degree of urinary phosphate excretion) may not always correlate with the onset of nephrocalcinosis. XLH patients receiving burosumab, which has been hypothesized to eliminate the risk factors for NC, can still develop NC. It is important to continue screening patients treated with burosumab for nephrocalcinosis. In addition, more research is needed to better understand the risk factors that cause XLH-associated NC and determine whether children with XLH never exposed to conventional therapy will develop NC.